Computational and experimental assessment of solar air heater roughened with six different baffles. (October 2021) - Sharma, Sachin; Das, Randip Kumar; Kulkarni, Kishor
Abstract: The present study emphasizes on a comparative assessment of solar air heater (SAH) roughened with six different baffles viz. Transverse, inclined transverse, dimple, inclined dimple, arc and sine wave, using computational fluid dynamics (CFD) analysis. The comparison has performed to investigate the augmentation in the heat transfer and friction factor of SAH with different baffles. The CFD study has been accomplished by varying Reynolds number (Re) from 3000 to 18000 whereas, Relative roughness pitch ( P / e =10) and Relative roughness height ( e / D h = 0.271) were kept fixed. Flow patterns by varying (Re), local and average Nusselt number, local and average friction factor, thermo-hydraulic performance (THP) have reported and elaborated. The computational results have verified by performing experiments on the same set of operating and geometric parameters. The deviation among numerical and experimental results of T H P have found +11%, which are in acceptable range. The results reveals that the positioning and shape of baffle unswervingly affect the T H P of the solar air heater. The maximum T H P of 2.05 has been recorded with a sine wave shape baffles at Re = 15000. The sine wave baffle shape has judged as the best among the studied baffles on a given range of operating and geometric parameters.